The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-301595/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corneal nerve loss in patients with TIA and acute ischemic stroke in relation to circulating markers of inflammation and vascular integrity

Abstract: Background Vascular and inflammatory mechanisms are implicated in the development of cerebrovascular disease and corneal nerve loss occurs in patients with transient ischemic attack (TIA) and acute ischemic stroke (AIS). We have assessed whether serum markers of inflammation and vascular integrity are associated with the severity of corneal nerve loss in patients with TIA and AIS. Methods Corneal confocal microscopy (CCM) was performed to quantify corneal nerve fiber density (CNFD), corneal nerve branch dens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Tear IL-6 level was shown to be inversely correlated with corneal nerve density in patients with bacterial keratitis [50]. The circulating level of IL-6 was significantly associated with corneal nerve fiber loss in patients with transient ischemic attack and acute ischemic stroke [51]. Moreover, an elegant study by Chucair-Elliott et al [52] reported that IL-6 was increased in the murine cornea after herpes simplex virus (HSV) infection, and that IL-6 suppression by either neutralizing Ab or dexamethasone reduced corneal nerve regression, thereby preserving sensation in HSV keratitis.…”
Section: Discussionmentioning
confidence: 94%
“…Tear IL-6 level was shown to be inversely correlated with corneal nerve density in patients with bacterial keratitis [50]. The circulating level of IL-6 was significantly associated with corneal nerve fiber loss in patients with transient ischemic attack and acute ischemic stroke [51]. Moreover, an elegant study by Chucair-Elliott et al [52] reported that IL-6 was increased in the murine cornea after herpes simplex virus (HSV) infection, and that IL-6 suppression by either neutralizing Ab or dexamethasone reduced corneal nerve regression, thereby preserving sensation in HSV keratitis.…”
Section: Discussionmentioning
confidence: 94%
“…49 The circulating level of IL-6 was signi cantly associated with corneal nerve ber loss in patients with transient ischemic attack and acute ischemic stroke. 50 Moreover, an elegant study by Chucair-Elliott et al 51 reported that IL-6 was increased in the murine cornea after herpes simplex virus (HSV) infection, and that IL-6 suppression by either neutralizing Ab or dexamethasone reduced corneal nerve regression, thereby preserving sensation in HSV keratitis. This notion that IL-6 contributes to corneal nerve degeneration is consistent with our ndings.…”
Section: Discussionmentioning
confidence: 99%